Distributed Architecture for Monitoring Urban Air Quality: A Systems Engineering Approach. Issue 1 (30th September 2020) - Unger, Adrian; Shean, Dylan; da Silva, Fabio G; Nguyen, Jennifer; Beebe, Laura B; Dewire, Philip; Grzelak, Stephen; McDermott, Tom
Abstract: The United Nations' environment program has selected the fight against air pollution as the topic for 2019's World Environment Day to raise the awareness of world's population for the fact that 7 million people worldwide die each year due to diseases associated to low air quality (UN Environment 2019) This paper summarizes the result of a project to support the development of a new architecture of global sensing devices for air quality and other earth science challenges. the project goal is to build a multi‐resolution unified picture of air quality using existing and potentially new technologies, allowing not only governments, but also scientists and regular citizens to contribute and have access to the information generated. This approach will potentially enhance real‐time monitoring and rapid reaction to degraded air quality events, or even better forecast events to take more efficient preventive actions. The project brought together NASA scientists and systems engineering students to conduct an initial system engineering analysis to build a high‐level system architecture. The effort helped to pave the way for further detailed engineering design and support the development of a testbed for early system verification and validation.